TARGET2 and central bank balance sheets - Karl Whelan (University College Dublin, UCD School of Economics, 2013)
The euro area's TARGET2 payments system has featured heavily in academic and popular discussions of the euro crisis. Some of this commentary has described the system as being responsible for a secret bailout of Europe's periphery. Another common theme has been that the system has built up large credit risks for Germany should the euro break up. This paper discusses the TARGET2 system, focusing in particular on how it impacts the balance sheets of the central banks that participate in the system. It discusses the factors driving TARGET2 balances, considers some counterfactual cases in which euro area monetary policy operated differently, examines the risks to Germany and considers proposals for settlement of these balances.
Keywords: 330